Micropropagation of “KL1” date palm (Phoenix dactylifera L.) - Noppharat Intha (2020)
Copyright © 2020. This is an open access article, production and hosting by Kasetsart University of Research and Development institute on behalf of Kasetsart University. Date palm (Phoenix dactylifera L.) is one of the most economically important fruit crops in many Arab countries. Recently, date palm cv. KL1 was developed and subsequently cultivated in many parts of Thailand. However, male and female trees could not be clearly distinguished until trees were flowering, and it should be propagated by tissue culture to obtain true-to-type plants. This study investigated the propagation of cv. KL1 female plants using a tissue culture technique. Offshoots aged 2 yr from mother plants were selected and surface sterilized in 0.1% mercuric chloride and 1% sodium hypochlorite. The dissected shoots were then cultured on modified Murashige and Skoog (MS) medium supplemented with 100 mg/L 2,4-dichlorophenoxyacetic acid (2,4-D) and 3 mg/L kinetin and 1 mg/L 6-benzylaminopurine (BAP), then cultured under dark conditions. Initiated callus formation was observed after 7 mth of culture. The embryogenic callus cultured in MS liquid medium supplemented with 6 mg/L 2,4-D produced the most somatic (2.59 g) growth at 1 mth. The somatic embryos were proliferated to new plantlets on MS medium, until 5 cm tall. In the final stage, root induction and elongation on MS medium supplemented with 0.9 mg/L 1-naphthaleneacetic acid induced the maximum number of roots (5.2) at 2 mth.